Africa's Contemporary Global Migrations: Patterns, Perils, and Possibilities - Paul Tiyambe Zeleza (Journal of Global Initiatives, 2010)
The literature on international migration is dominated by economic and political perspectives. This paper begins with the culturalist readings to remind ourselves that there is more to international migration than the search for greener pastures or flight from political terror. It is about the movement of human beings, a story that is as old as humanity itself, going back to the great migrations within and out of Africa to populate the planet. But those who advance the culturalist perspectives also need to be reminded that in our contemporary world more often than not people migrate to sell their labor power and that the patterns of migration, labor procurement and utilization are conditioned by the dynamics of capitalist development, expansion, and accumulation. This is an argument for interdisciplinarity, the need for multiple perspectives on the exceedingly complex phenomenon of international migration.